PENGARUH PEMBELAJARAN DALAM JARINGAN (DARING) TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PAI DI SMP ISLAM SERBA BAKTI SURYALAYA - Astuti, Pravitasari Puji; Santoso, Try Riduwan; Kurniawan, Ase (Prodi PAI IAILM Suryalaya, 2021)
This study aims to determine the effect of online learning on students' interest in learning in PAI subjects at Serba Bakti Islamic Junior High School. The method in this study uses a descriptive method with a quantitative approach. The study population was 129 students with a sample of 23 students, sampling using the Purposive Sampling Technique. Data collection techniques using questionnaires, interviews, observations, and documentation. Quantitative data processing is completed through descriptive data processing with Spearman rank correlation ( rs ). Based on the results of processing the questionnaire data regarding online learning, the average value was calculated at 48.04, in the interval 48.68 - 53.24, so it was classified as good. Interest in learning got an average score of 45.30, which was in the interval from 43.66 to 48.99, so it was quite enough. The effect of online learning on students' learning interest in PAI subjects at SMP Islam Serba Bakti has a significant influence with sufficient classification, as evidenced by the value of rs 0.52 in the interval 0.41-0.60, and the results of the calculation of tcount 3,005 ttable 2,080. Then Ha is accepted and HO is rejected. Online learning affects students' learning interest in PAI subjects by 27%, the remaining 73% is determined by other factors.